Simultaneous Chain-Growth and Step-Growth Polymerization of Methoxystyrenes by Rare-Earth Catalysts - Shi, Xiaochao; Nishiura, Masayoshi; Hou, Zhaomin (Angewandte Chemie International Edition, 2016)
The simultaneous chain‐growth and step‐growth polymerization of a monomer is of great interest and importance because it can produce unique macromolecules which are difficult to prepare by other means. However, such a transformation is usually difficult to achieve in one polymerization system because chain‐growth polymerization and step‐growth polymerization proceed by different reaction mechanisms. Reported here is the simultaneous chain‐growth and step‐growth polymerization of para‐ and meta‐methoxystyrenes catalyzed by half‐sandwich rare‐earth alkyl complexes, and the step‐growth polymerization proceeds by the C−H polyaddition of anisyl units to vinyl groups. This unprecedented transformation affords a new family of macromolecules containing unique alternating anisole‐ethylene sequences. In contrast to para‐ and meta‐methoxystyrenes, ortho‐methoxystyrene exclusively undergo syndiospecific, living chain‐growth polymerization by continuous C=C bond insertion to give perfect syndiotactic poly(ortho‐methoxystyrene) with high molecular weight and narrow polydispersity (rrrr >99 %, Mn up to 280 kg mol−1, Mw/Mn <1.10). Growth spurt: Both continuous C=C bond insertion and C−H addition of anisole units to vinyl groups took place in the polymerization of para‐ and meta‐methoxystyrenes when catalyzed by a half‐sandwich rare‐earth catalyst, thus affording novel macromolecules containing multiple branches of alternating anisole‐ethylene sequences. In contrast, the polymerization of ortho‐methoxystyrene occurred exclusively through continuous C=C insertion without involving C−H activation.